Perubahan Indeks Kenyang Caplak Haemaphysalis bispinosa (Acari, Ixodidae) Selama Masa Makan - Winaruddin Winaruddin (Universitas Jambi, 2014)
The objective of this research was to know various engorgement indices and durationof attachment of female Haemaphysalis bispinosa. Two feeding experiment were designedusing the following female-male ratio 1:1 and 30:1. At same time every day up to detachmentthe body length, width and depth of females were measured using a caliper to the determine ofbody volume. Fed body weights of the females were weighed on a electric balance. The resultof this research indicates that rate of engorgement indices in females (1:1 ratio) and (30:1 ratio)increased with increasing duration of attachment (P< 0.05) and the relationship betweenduration of tick attachment was above 92%. The feeding rate of females of the 30:1 ratio waslower than that of 1:1 ratio ones up to the 72 hours in the duration attachment.